2013
DOI: 10.1111/jai.12328
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-RFLP based test for distinguishing European and Atlantic sturgeons

Abstract: Summary The two sister species of Atlantic and European sturgeon are difficult to distinguish solely by morphological traits, especially in their early life stages. A simple PCR‐RFLP based test was developed, enabling easy identification of specimens belonging to both species. The application of two restriction enzymes (BtsI and BsrDI) allowed the clear and unambiguous discrimination of 132 specimens of Atlantic and European sturgeon. The test should prove particularly useful with regard to the sturgeon restit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…The PCR‐RFLP method described by Panagiotopoulou et al . () was used to screen the contemporary samples for this polymorphism.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR‐RFLP method described by Panagiotopoulou et al . () was used to screen the contemporary samples for this polymorphism.…”
Section: Methodsmentioning
confidence: 99%
“…A minimum of six clones per PCR product were sequenced using M13 universal primers and checked for consistency. The PCR-RFLP method described by Panagiotopoulou et al (2014) was used to screen the contemporary samples for this polymorphism.…”
Section: Mitochondrial Dna and Microsatellite Analysismentioning
confidence: 99%
“…) has been universally considered to be closely related to, if not synonymous with (Artuykhin and Vecsei, ), the European sea sturgeon, A. sturio . This is due to the substantial morphological similarity of the two species (Vladykov and Greeley, ; Vasil'eva, ; see Desse‐Berset, for morphological characters separating the two species, and Panagiotopoulou et al., for methods of genetic discrimination). Additionally, these species share similar karyotypes and cytogenetic features (Fontana et al., ) and in all cladistic analyses of sturgeon relationships using both morphological and molecular data, the two are recovered as sister‐taxa.…”
Section: Taxonomy and Phylogenymentioning
confidence: 99%
“…In genetic studies regarding sturgeons the PCR-RFLP markers were mainly used in two directions: to assess the genetic diversity of sturgeon populations [40,41] and for species identification and implicit for caviar traceability [42,43]. Wolf et al [42] has identified species specific restriction profiles in a fragment from the mitochondrial gene cytochrome b (cyt b) in 10 species from Acipenser and Huso genera.…”
Section: Pcr-rflpmentioning
confidence: 99%
“…A similar study was performed by Ludwig et al [44] for 22 sturgeon species, an accurate identification being possible by analyzing the restriction profiles resulted consequently the action of five REs on a fragment of 1121 bp from cyt b gene. Panagiotopoulou et al [43] proposed a molecular method based on PCR-RFLP to distinguish between Atlantic (Acipenser oxyrinchus) and European (A. sturio) sturgeon. The discrimination between the two species is difficult to be done exclusively by morphological traits, especially in their early life stages, while the application of two REs allowed the clear and unambiguous discrimination of 132 specimens of Atlantic and European sturgeon.…”
Section: Pcr-rflpmentioning
confidence: 99%